Streptococcus pneumoniae as a Cause of Community-Acquired Pneumonia: Changes Over the Past 100 Years. (4th October 2017) - Abers, Michael; Musher, Daniel; Bartlett, John G
Abstract: Background: In the preantibiotic era, Streptococcus pneumoniae (Sp) was responsible for >90% of community-acquired pneumonia (CAP). Modern studies identify Sp in only 5–14% of CAP in the United States (US) and Canada and 15–35% in Europe. Methods: PubMed and Google Scholar were searched for studies reporting the etiologic spectrum of CAP in adults in the US, Canada, or Europe. Inclusion of each study required the use of a conventional case definition for CAP and application of standard microbiologic techniques in >50% of cases. Reports on a single subpopulation (immunocompromised, elderly, etc.) or clinical setting (ICU, outpatient, etc.) were excluded. Results: Thirty-one studies from the US and Canada (21, 315 patients) and 41 from Europe (25, 183 patients) met inclusion criteria. Included studies were published between 1917 and 2015. In the USA and Canada, the proportion of cases caused by Sp decreased significantly over time (Figure 1A) and was inversely related to the proportion of patients with antibiotic use prior to hospital admission (Pearson's correlation coefficient -0.76 [95% confidence interval −0.48 to −0.90, P < 0.001]). In the US and Canada, the frequency of Sp has continued to decline during the past 4 decades; in contrast, the frequency of Sp has remained stable in Europe during this time (Figure 1B). Conclusion: The proportion of CAP caused by Sp has declined dramatically in the US and Canada during the past 100 years. The initial decline between 1940 and 1965 may be explained by availability of antibiotics. Potential factors contributing to the continued decline include widespread pneumococcal vaccination and declining rates of smoking. The higher frequency of Sp in Europe may be due to lower vaccination rates in adults and higher rates of smoking. Limitations of the present study include heterogeneity among studies in illness severity, comorbidities, microbiologic testing and prior antibiotic use. Disclosures: All authors: No reported disclosures.